2020
DOI: 10.1016/j.matpr.2020.10.086
|View full text |Cite|
|
Sign up to set email alerts
|

WITHDRAWN: Analysis of ‘earlyR’ epidemic model and time series model for prediction of COVID-19 registered cases

Abstract: The COVID-19 is an epidemic that causes respiratory infection. The forecasted data will help the policy makers to take precautionary measures and to control the epidemic spread. The two models were adopted for forecasting the daily newly registered cases of COVID-19 namely ‘earlyR’ epidemic model and ARIMA model. In earlyR epidemic model, the reported values of serial interval of COVID-19 with gamma distribution have been used to estimate the value of R 0 and ‘projections’ package is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…[21,24,43,49,50,63] The R package earlyR is the frequentist equivalent of EpiEstim, and therefore returns estimates that are only data-driven, but it is not set up to estimate time-varying reproduction numbers. [21,43,49,50,74] EpiFilter can use data before and beyond time t to estimate R t , which means that in addition to real-time estimation it can facilitate more robust retrospective estimation, particularly in low incidence settings. [24,63] In EpiEstim, the SI distribution can be specified as parametric (where only the mean and standard deviation are required), non-parametric (where the whole discrete distribution is provided), or "uncertain", where a range of potential SIs are considered.…”
Section: Other Input Data or Methods Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,24,43,49,50,63] The R package earlyR is the frequentist equivalent of EpiEstim, and therefore returns estimates that are only data-driven, but it is not set up to estimate time-varying reproduction numbers. [21,43,49,50,74] EpiFilter can use data before and beyond time t to estimate R t , which means that in addition to real-time estimation it can facilitate more robust retrospective estimation, particularly in low incidence settings. [24,63] In EpiEstim, the SI distribution can be specified as parametric (where only the mean and standard deviation are required), non-parametric (where the whole discrete distribution is provided), or "uncertain", where a range of potential SIs are considered.…”
Section: Other Input Data or Methods Modificationmentioning
confidence: 99%
“…[45] The scoping review identified additional methodological or data-related issues. These led to the development of methods that are more appropriate for use during periods of low incidence, [21,24,43,49,50,63] or offer alternatives to allow less subjective and more flexible inputs into EpiEstim, e.g. the prior for R t , the SI distribution, or an alternative way of temporally smoothing R t estimates.…”
Section: Plos Digital Healthmentioning
confidence: 99%
“…The COVID-19 is fast and lasts a long time [ 32 ], so this paper selects quarterly economic data before and after the COVID-19(September 2019 to December 2020). The data used for calculating the economic indicators were obtained from the Statistical Yearbook of Beijing, Tianjin and Hebei Province.…”
Section: Methodsmentioning
confidence: 99%
“…The ARIMA model was more capable in the prediction of COVID-19 cases compared to other prediction models, including instance support vector machine (SVM) and wavelet neural network (WNN). Existing India COVID-19 data were also used for forecasting new daily confirmed cases using two models, earlyR and ARIMA [16]. A comparison between the two models showed that the ARIMA model provided better accuracy than that of the earlyR model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They were used to predict the future dynamics of malaria [5,6], influenza [7][8][9], tuberculosis [10,11], and other infectious diseases [12,13]. Recently, timeseries models were used to forecast the dynamics of COVID-19 in the USA [14], Italy [14], India [15,16], and several other countries [17,18].…”
Section: Introductionmentioning
confidence: 99%